COMPARATIVE EFFICACY OF MICRODACYN AND DIOXIDIN IN PATIENTS WITH DIABETIC FOOT SYNDROME - Bobobekov, A.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Diabetic foot syndrome is the main cause of hospitalization and mortality in patients with diabetes mellitus, of which 25% have purulent-necrotic lesions of the feet during their lives. Material and methods. The results of the treatment of 116 patients with diabetic foot syndrome who were treated and examined in the Department of Surgical Infection of the Multidisciplinary Clinic of the Tashkent Medical Academy are analyzed. Evaluation of the results of treatment of patients with purulent-necrotic processes of diabetic foot syndrome was carried out, first of all, on the basis of a study of the general condition of patients and data from the local course of the process. Results. The combined use of Microdacyn in the complex treatment of diabetic foot syndrome in phase I of the wound process leads to a decrease in microbial contamination, faster completion of the stages of inflammation, and optimizes the processes of reparative tissue regeneration. Conclusion. The proposed method can be used as a preoperative preparation of purulent-necrotic wounds in patients with diabetic foot syndrome to the final method of closure with the use of plastic surgery.